AKIBAT HUKUM ORANG HILANG (MAFQUD) TERHADAP HARTA BENDA DAN PENYELESAIAN KEWARISAN DALAM ISLAM - Agung Widya Yudhistira; agung widya yudhistira (Universitas Sriwijaya, 2021)
Mafqud is a person whose news is interrupted so that his life and death are not known. There are so many catastrophic events experienced by humans, be it natural disasters or accidents that can claim lives, so that some of these victims can be identified as dead and some whose whereabouts are unknown or missing. With this condition, there is confusion in determining the legal status, inheritance rights and who can inherit the property of the missing person. Therefore, the main problem in this study is how to determine the legal status of missing persons (mafqud), what are the legal consequences of the occurrence of missing persons on property for both heirs and heirs (mafqud), as well as the role of a notary in the distribution of the inheritance of missing persons (mafqud). ). This research is a normative research that is descriptive and explanatory with a statutory approach, cases, and uses secondary data sources obtained from primary legal materials, secondary legal materials and tertiary legal materials. The data collection of this research was carried out by means of a literature study. Based on the results of the discussion of the main issues, the following conclusions can be drawn: in determining the legal status of the missing person (mafqud) it is through the determination of the Religious Court that the mafqud is considered dead based on applicable laws and regulations both from KHI and the opinion of priests from various schools of thought. Regarding the assets of the mafqud, it is suspended or detained until the time limit according to the regulations and the existence of a court order. The role of a notary in this inheritance is to make a Certificate of Inheritance Rights (SKHM) in accordance with his authority in the Law on Notary Positions.